Ipsilateral Supracondylar Fracture and Forearm Bone Injury in Children: A Retrospective Review of Thirty one Cases - Dhoju, D; Shrestha, D; Parajuli, N; Dhakal, G; Shrestha, R (Kathmandu University Medical Journal, 2012)
Background Supracondylar fracture and forearm bone fracture in isolation is common musculoskeletal injury in pediatric age group But combined supracondylar fracture with ipsilateral forearm bone fracture, also known as floating elbow is not common injury. The incidence of this association varies between 3% and 13%. Since the injury is rare and only limited literatures are available, choosing best management options for floating elbow is challenging. Method In retrospective review of 759 consecutive supracondylar fracture managed in between July 2005 to June 2011, children with combined supracondylar fracture with forearm bone injuries were identified and their demographic profiles, mode of injury, fracture types, treatment procedures, outcome and complications were analyzed. Result Thirty one patients (mean age 8.91 yrs, range 2-14 yrs; male 26; left side 18) had combined supracondylar fracture and ipsilateral forearm bone injury including four open fractures. There were 20 (64.51%) Gartland type III (13 type IIIA and 7 type III B), seven (22.58 %) type II, three (9.67 %) type I and one (3.22 %) flexion type supracondylar fracture. Nine patients had distal radius fracture, six had distal third both bone fracture, three had distal ulna fracture, two had mid shaft both bone injury and one with segmental ulna with distal radius fracture. There were Monteggia fracture dislocation, proximal ulna fracture, olecranon process fracture, undisplaced radial head fracture of one each and two undisplaced coronoid process fracture. Type I supracondylar fracture with undisplaced forearm were treated with closed reduction and long arm back slab or long arm cast. Displaced forearm fracture required closed reduction and fixation with Kirschner wires or intramedullary nailing. Nineteen patients with Gartland type III fracture underwent operative intervention. Among them nine had closed reduction and K wire fixation for both supracondylar fracture and forearm bone injury. One patient with closed reduction and long arm cast application for both type III supracondylar fracture and distal third radius fracture developed impending compartment syndrome and required splitting of cast, remanipulation and Kirschner wire fixation. There were three radial nerve, one ulnar nerve and one median nerve injury and two postoperative ulnar nerve palsy. Three patients had pin tract related complications. Among type III, 16 (80%) patients had good to excellent, two had fair and one gad poor result in terms of Flynn’s criteria in three months follow up ConclusionDisplaced supracondylar fracture with ipsilateral displaced forearm bone injuries need early operative management in the form of closed reduction and percutaneous pinning which provides not only stable fixation but also allows close observation for early sign and symptom of development of any compartment syndrome.DOI: http://dx.doi.org/10.3126/kumj.v9i2.6280 Kathmandu Univ Med J 2011;9(2):11-16